Pengembangan Modul Pembelajaran Matematika pada Materi Penjumlahan dan Pengurangan Bilangan Bulat dengan Menggunakan Model Neutralization on a Number Line (NNL) - Milda Maulida; Puspita Sari; Swida Purwanto (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to produce learning resources in the form of mathematics modules for students at the junior high school level. This mathematics module was created because the teaching materials used were still not motivating students to learn mathematics. This was reinforced by the results of the analysis of the students' needs, namely as many as 65% of students stated that the available teaching materials did not motivate students to learn mathematics. Based on the needs analysis, the material developed is the material for addition and subtraction of integers using the neutralization on a number line (NNL) model. This research and development uses the RnD method which refers to the Borg & Gall model. The developed mathematics module has gone through media expert validation with an average percentage value of 81% with a very good category, and validation of material and language experts with an average percentage value of 92% with an excellent category. Then conducted trials on teachers and students. In the results of the teacher trial, the average percentage value was 98% with the very good category. In the test results of small group students, an average percentage value of 85% was obtained with the very good category and the large group student trials obtained an average percentage value of 85% with the very good category. So that the developed mathematics module is feasible to be used in the learning process in schools with an overall average of 88%.